Stock Price Volatility Out of LQ45 February - July 2022 Period - Nelmida, Nelmida; Dewi, Nurlita; Br. Bangun, Susan Oktaviani (Jurnal Manajemen, 2023)
Volatility is the fluctuation of returns in a certain period, if the fluctuations in returns have a large variation, then the possibility of a risk that will occur is greater, and vice versa if the fluctuation of risk is smaller, the probability that the risk that will occur will be smaller. Analysis of stock price volatility from stock indexes is needed to facilitate investors in making investment decisions. This study aims to provide an overview of the volatility of securities owned by investors towards shares owned in the LQ45 stock index group which have the potential to receive expected returns or have risk potential. Also knowing how much value can be generated from profits and how much risk will be borne by investors. This study uses descriptive comparative and quantitative research methods using secondary data, and the model used to assess stock volatility is the Baskin method (1989). Based on the research results, there is a difference in the volatility of the stock prices of companies that enter and leave LQ45 for the period 1 February – 31 July 2022. The scope of the research is only companies that enter and leave LQ45 for the period 1 February to 31 July 2022, so the number of samples used is limited and the research results cannot be generalized, and. The model used to assess stock volatility is the Baskin method (1989). Novelty is the uniqueness of the research is volatility of stocks leaving LQ 45 during February-July 2022 Keywords: Stock volatility; LQ 45; investors